2007
DOI: 10.1007/s00405-007-0383-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of auricular keloids: review of different treatment modalities and proposal for a therapeutic algorithm

Abstract: Keloids are abnormal wound reactions of connective tissue. Auricular keloids can develop as a result of, e.g., otoplasty, ear piercing, or skin trauma. A wide variety of therapeutic options exists, including surgery as primary treatment. Furthermore, there are medical, physical, radiotherapeutic and experimental options. The present paper focuses on the different techniques including the therapeutic outcome and quality rating for each chosen pathway. In addition to the experience of the university hospitals, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 60 publications
1
51
0
3
Order By: Relevance
“…Historically, a number of treatment modalities such as cryotherapy, 23 interferon 24 and veramapril 25 have been utilized for treating KD, with inconsistent levels of success. However, more recent treatments such as lasers, 26 intralesional steroid injections, 27 silicone gel, 28 5-fluorouracil (FU), 29 radiotherapy, 30 bleomycin, 31 imiquimod, 32 photodynamic therapy (PDT), 33 electrical stimulation (ES) 34 and surgery 35 have also been used in the management of KD, but not all have shown efficacy in ethnic pigmented skin. These commonly available and newly emerging treatment modalities (Table 3) will be discussed in detail below.…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, a number of treatment modalities such as cryotherapy, 23 interferon 24 and veramapril 25 have been utilized for treating KD, with inconsistent levels of success. However, more recent treatments such as lasers, 26 intralesional steroid injections, 27 silicone gel, 28 5-fluorouracil (FU), 29 radiotherapy, 30 bleomycin, 31 imiquimod, 32 photodynamic therapy (PDT), 33 electrical stimulation (ES) 34 and surgery 35 have also been used in the management of KD, but not all have shown efficacy in ethnic pigmented skin. These commonly available and newly emerging treatment modalities (Table 3) will be discussed in detail below.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…69 It may be used in polytherapy to prevent recurrence of KD after surgical excision. 32 One study compared topical imiquimod with steroid injection following earlobe keloid excision in four patients. 70 Two patients had recurrences, but the small, uncontrolled nature of the study means that it is difficult to draw direct comparisons.…”
Section: Imiquimodmentioning
confidence: 99%
“…Studies have found that keloid treatment is most effective when using multiple modalities, but there is still much controversy as to what is the optimal treatment [7]. Surgical excision without adjuvant therapy of the keloids, irrespective of the location, is said to have a recurrence rate between 45% and 100% [9].…”
Section: Discussionmentioning
confidence: 99%
“…10 Radiotherapy has been hypothesized to destroy fibroblasts, connective tissue stem cells, and acute inflammatory cells. 16 Side effects include hyperpigmentation, pruritus, and erythema. Radiotherapy, as a single-treatment modality, was found to have variable response rates of 10 to 94 percent.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a large review study, the crude risk for developing radiation-induced malignancy following radiotherapy administered for keloid treatment was found to be one in 1348. 24 The risk may be underestimated, however, as patients were not followed up for decades.…”
Section: Discussionmentioning
confidence: 99%